2020
DOI: 10.3390/jcp1010003
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Anti-Evasion Malware Triggers Using Automated Sandbox Reconfiguration Techniques

Abstract: Malware analysis is fundamental for defending against prevalent cyber security threats and requires a means to deploy and study behavioural software traits as more sophisticated malware is developed. Traditionally, virtual machines are used to provide an environment that is isolated from production systems so as to not cause any adverse impact on existing infrastructure. Malware developers are fully aware of this and so will often develop evasion techniques to avoid detection within sandbox environments. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The evaluation confirmed that parameter-tuned LightGBM in the 3rd stage detected DoH traffic generated by Pad-Crypt [22], Sisron [23], Tinba [24], [25], and Zloader [26] with 99.12% accuracy. In addition, parameter-tuned LightGBM in the 1st stage filtered DoH traffic with 99.92% accuracy, and parameter-tuned CatBoost in the 2nd stage recognized suspi- cious DoH traffic with 99.97% accuracy.…”
Section: Introductionsupporting
confidence: 57%
“…The evaluation confirmed that parameter-tuned LightGBM in the 3rd stage detected DoH traffic generated by Pad-Crypt [22], Sisron [23], Tinba [24], [25], and Zloader [26] with 99.12% accuracy. In addition, parameter-tuned LightGBM in the 1st stage filtered DoH traffic with 99.92% accuracy, and parameter-tuned CatBoost in the 2nd stage recognized suspi- cious DoH traffic with 99.97% accuracy.…”
Section: Introductionsupporting
confidence: 57%
“…One challenge in any sandbox monitoring agent is whether the agent itself is compromised or interferes with the malware execution. Many malware samples look for environment parameters that may suggest they are running in a sandbox [19], such as the present of agent.py which is used by Cuckoo or the phrase "VMware" occurring in the Windows registry. We found that our various data collectors would terminate at different times, which is likely related to this.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mimicking legitimate behavior is a widely used strategy by todays malware ( Bulazel & Yener, 2017 ; Alaeiyan, Parsa & Conti, 2019 ; Or-Meir et al, 2019 ; Afianian, Niksefat & Sadeghiyan, 2019 ; Mills & Legg, 2020 ; Amer, El-Sappagh & Hu, 2020 ). In addition, evasion behaviors have been observed in both benign and malicious classes ( Galloro et al, 2022 ).…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…By analyzing 45,375 malware samples, Galloro et al (2022) concluded that the use of evasion mechanisms has increased among malware by 12% over the past ten years, and 88% of malicious software can perform new evasion behaviors rather than the older ones. Evasive malware instances either imitate legitimate behaviors or violently interrupt the execution in sandboxed execution conditions ( Bulazel & Yener, 2017 ; Alaeiyan, Parsa & Conti, 2019 ; Or-Meir et al, 2019 ; Afianian, Niksefat & Sadeghiyan, 2019 ; Mills & Legg, 2020 ). Additionally, Galloro et al (2022) in their work, reported that evasion behaviors have picked up in both malware and benign instances because those evasion techniques have been originally developed for a legitimate purpose, such as to prevent reversing, and protect intellectual property.…”
Section: Introductionmentioning
confidence: 99%